Association between purpose in life and healthcare use among women and men in Germany: cross-sectional analysis of the nationally representative German Socio-Economic Panel (GSOEP) study - Hans-Helmut König; André Hajek (BMJ Open, 2022)
Objectives It remains almost unknown whether purpose in life is associated with healthcare use (HCU) in general. Therefore, the goal of this study was to examine the association between purpose in life and HCU (in terms of frequency of outpatient physician visits and hospitalisation) stratified by sex.Design Cross-sectional study.Setting and participants A representative sample of the general adult population in Germany (n=1238; collected from September 2020 to February 2021); taken from the innovation sample of the German Socio-Economic Panel.Outcome measures The frequency of outpatient physician visits in the past 3 months was used as first outcome measure. Hospitalisation in the last 12 months was used as the second outcome measure. Purpose in life was quantified by means of the subscale ‘purpose in life’ of the six-factor model of psychological well-being. Covariates were selected based on the Andersen model.Results Average purpose in life equaled 4.5 (SD: 0.8; ranging on a scale from 1 to 6, with higher values indicating higher purpose in life). Adjusting for various potential confounders, regressions revealed that higher purpose in life was associated with an increased frequency of outpatient physician visits in the past 3 months among women (IRR 1.16, 95% CI:1.03 to 1.30), but not men (IRR 0.96, 95% CI 0.87 to 1.07). In contrast, higher purpose in life was associated with in an increased likelihood of hospitalisation among men (OR 1.40, 95% CI 1.02 to 1.93), but not women (OR 1.03, 95% CI 0.79 to 1.34).Conclusion Even after adjusting for various potential confounders, there was still a gender-specific association between higher purpose in life and increased HCU. This knowledge may assist in addressing individuals at risk for underuse or overuse of healthcare services.